2015
DOI: 10.1152/jn.00449.2015
|View full text |Cite
|
Sign up to set email alerts
|

Transspinal constant-current long-lasting stimulation: a new method to induce cortical and corticospinal plasticity

Abstract: Knikou M, Dixon L, Santora D, Ibrahim MM. Transspinal constant-current long-lasting stimulation: a new method to induce cortical and corticospinal plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 85 publications
3
50
0
Order By: Relevance
“…; Knikou et al . ). However, they may well reflect differences in the current density and its gradient within the spinal cord in conditions of tsDCS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Knikou et al . ). However, they may well reflect differences in the current density and its gradient within the spinal cord in conditions of tsDCS.…”
Section: Discussionmentioning
confidence: 97%
“…; Knikou et al . ). However, marked post‐activation depression in pathways between cutaneous afferents and dorsal horn neurons (Hammar et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another promising NIBS technique involves the delivery of 40 min of constant current stimulation to the spinal cord [106]. Long-lasting transspinal constant current stimulation (ts-CCS) alters cortical, corticospinal, and spinal plasticity in uninjured participants.…”
Section: New Opportunities For Nibs To Promote Motor Recovery In Scimentioning
confidence: 99%
“…Long-lasting transspinal constant current stimulation (ts-CCS) alters cortical, corticospinal, and spinal plasticity in uninjured participants. Knikou et al [106] found that both cathodal tsCCS and anodal tsCCS decreased afferent-mediated MEP facilitation, increased MEP amplitudes, and decreased transspinal-evoked potentials (TEPs) of knee flexors. Further, cathodal tsCCS increased TMS-mediated tibialis anterior flexor reflex facilitation, while anodal tsCCS decreased TMS-mediated TA flexor reflex facilitation and decreased post-activation depression of TEPs for the soleus H-reflex.…”
Section: New Opportunities For Nibs To Promote Motor Recovery In Scimentioning
confidence: 99%